The Effect of Unemployment, Poverty and Income Inequality on Economic Growth in Indonesia - YULIA, Resa Adhima; DEWI, Dita Dismalasari (Journal of Tourism Economics and Policy, 2025)
This study aims to analyze the impact of unemployment, poverty, and income inequality on economic growth in Indonesia. This study uses an associative quantitative approach. The data used in this study is secondary data from the Central Statistics Agency. The analysis method used is panel data regression by combining cross-sectional and time-series data for the 2020-2024 period from 34 provinces in Indonesia, and the model used is the Fixed Effect Model. The results of this study indicate that the unemployment rate has a negative and significant impact on economic growth, with a coefficient value of -3.083497 and a probability value of 0.0000. Conversely, poverty has a positive but insignificant impact on economic growth, with a coefficient value of 0.706846 and a probability value of 0.0779. In addition, income inequality has a negative and significant impact on economic growth, with a coefficient value of -84.82510 and a probability value of 0.0076. The simultaneous test shows that these three variables collectively have a significant impact on economic growth, with an Fstatistic probability value of 0.00000. This study concludes that although poverty does not have a significant impact on economic growth, reducing unemployment and income inequality should be key factors in supporting sustainable economic development in Indonesia.